STERNE/YORICK, THE SENTIMENTAL TRAVELLER AND CONTEMPORARY TRAVEL WRITING STUDIES: PROBLEMATISING THE CRITICAL AFTERLIFE OF A SENTIMENTAL JOURNEY - Jakub Lipski, Jakub Lipski (Porównania, 2019)
This article addresses two critical topoi in contemporary travel writing studies – Laurence Sterne’s agency in the so-called paradigm shift from the scientific to the subjective in eighteenth- century travel writing and the vague concept of “Sternean/Shandean fashions”, which has tended to be used as an umbrella term for stylistic idiosyncrasies in post-1768 travel writing. The former is approached as reflective of a style of reception that yearns to establish a myth of origin at the cost of historical accuracy. The latter is analysed with reference to the East Central European notion of sternizm, and exemplifies a pattern of disconnection, where a critical term derived from a name begins an autonomous life of its own and loses contact with the point of origin.